Greengram Seed Microflora under Ambinent Storage - NAZNIN BEGUM,; P.K. BORAH,; DAISY SENAPATY,; BIMAL RABHA, (Seed Research, 2026)
Understanding of the status of microflora associated with greengram (Vigna radiata) seeds is important. With this objective mungeban seeds (var. Pratap) were subjected to storage in metallic bin under ambient condition. Seed samples were drawn on 0, 90, 180 and 270 days intervel for identification of microflora and evaluation of their pathogenicity. Seed wash method showed no bacterial microflora; agar plate method showed 4 fungal isolates (SP-1, SP-2, SP-3 and SP-4) which were identified as Aspergillus flavus, A. niger, Penicillium spp. and Rhizoctonia solani, respectively. Pathogenicity test showed that all the four identified fungal species gradually reduced seed germination. There was no germination with increased inoculation period of 216 hr as against 90% germination in non-inoculated control. The study indicated that the associated fungal species was pathogenic.